Does Kangaroo Mother Care Reduce Anxiety in Postnatal Mothers of Preterm Babies? – A Descriptive Study from a Tertiary Care Centre in South India - Rao, Priyanka; R, Raajashri; Bethou, Adhisivam; Bhat, Vishnu; C, Palanivel (Journal of Nepal Health Research Council, 2019)
Background: To assess anxiety and depression among postnatal mothers of preterm babies and to evaluate whether Kangaroo mother care reduces their anxiety.Methods: This descriptive study was conducted in a tertiary care teaching hospital in south India. Anxiety and depression was assessed using Hospital Anxiety and Depression Scale in 2 groups of postnatal mothers (Pre Kangaroo mother care and post Kangaroo mother care) with 50 participants each and compared. Results: In the pre Kangaroo mother care group, abnormal sub scale scores were noted in 27 (54%) and 21 (42%) for anxiety and depression respectively. The mean Hospital Anxiety and Depression Scale anxiety subscale score was 10.1 (±4.5) and mean depression subscale score was 9.15 (±4.3) in the pre Kangaroo mother care group compared to 7.76 (± 4.8) and 7.24 (± 5.15) respectively in the post Kangaroo mother care group. The mean total Hospital Anxiety and Depression Scale score was significantly less in the post Kangaroo mother care group compared to pre Kangaroo mother care group. Conclusions: Mothers of preterm neonates experience significant anxiety and depression during the immediate postnatal period and Kangaroo mother care can reduce their stress. Keywords: Anxiety; depression; kangaroo mother care; newborn; preterm.